SURVEY OF WINDOWPANE OYSTER (PLACENTA PLACENTA) RESOURCES IN THE KAKINADA BAY - Murty, V Sriramachandra; Narasimham, K A; Venugopalam, W (Indian Journal of Fisheries, 2011)
An estimated population of live window-pane oyster of 8,945.3 tonnes and43,347.6 tonnes of shells of dead oyster is ;n the Kakinada Bay, spread out in anarea of 132 sq. km. The live oyster is confinsd to western and southern sides ofthe Bay which are known to be reh lively more productive. The shells of deadoyster are spread all over the Bay with very large concentration on the easternside. The fishermen remove window-pane oyster available on the southern andwestern sides during January-May and the catches are utilised mainly for manufactureof lime. It is suggested that extension of fishing season along vwith extensionof fishing ground to the eastern and central portions of the Bay will result ingreater yield of this resource. There is considerable scope in utilisation of thisresource by extracting pearls formed in them and also flesh being used as anitem of food.